Substance Use Education in Schools of Nursing: A Systematic Review of the Literature. Issue 3 (May 2018) - Smothers, Zachary; Reynolds, Victoria; McEachern, Mark; Derouin, Anne L.; Carter, Brigit M.; Muzyk, Andrew
Abstract : The authors systematically reviewed the nursing literature for articles describing substance use disorders (SUDs) education in schools of nursing. Five literature databases were searched, producing 3107 retrieved articles, of which 12 were included in this review. A Medical Education Research Study Quality Instrument score was calculated for each study. The included studies demonstrated that teaching nursing students about SUDs produced a positive impact on their attitudes, knowledge, and skills.